The Manifoldness of Traditional Knowledge: The Example of the Minangkabau Society in West Sumatra, Indonesia (KEMANUSIAAN The Asian Journal of Humanities, 2023)
In a fast-changing world, traditional knowledge is moved to the edge. In many fields of knowledge, there is no place for traditional knowledge. Often this wisdom is considered to be taboo and old-fashioned. However, it must be emphasised that it belongs to the cultural heritage of humankind. The authors intend to show the richness of traditional knowledge by focusing on one geographical area, namely West Sumatra. The essential fields of traditional knowledge in that area are illustrated and analysed. The authors focus on three types of traditional knowledge, namely philosophy, the judicial system, and traditional healing methods. They conducted qualitative research that included fieldwork and an analysis of relevant literature to deepen the knowledge. The main hypothesis was that the different spheres of traditional knowledge were interdependent. It was detected that the traditional Minangkabau culture has fascinating traditional knowledge that is worth to be preserved.